Increasing the Accuracy of Color Measurement System to Reduce Waste of Non-Standard Color Problems in Kraft Paper Production. - PANUPONG NUYOD, NARA SAMATTAPAPONG (Mathematical Statistician and Engineering Applications, 2022)
This research is divided into two parts. Part 1 aims to study the design of standard calibration values based on comparative data collection. of internal auditors according to the International Commission on Illumination (CIE) standards and used for statistical analysis in order to use the analysis results to increase the measurement accuracy of the Color Sensor measuring instrument; A device to control factors that affect measurements, such as paper speed, light, heat or impurities. and set a standard for the measurement of the company by referring to the quality inspection department that limits the accuracy of the measurement range that does not exceed ± 0.5 for use in reducing the non-standard color waste in the kraft paper production process in the company